A p38 mitogen-activated protein kinase inhibitor attenuates cardiotonic steroids-induced apoptotic and stress signaling in a Sw-71 cytotrophoblast cell line. Issue 11 (November 2015) - Ehrig, Jessica C.; Afroze, Syeda H.; Reyes, Michelle; Allen, Steven R.; Drever, Nathan S.; Pilkinton, Kimberly A.; Kuehl, Thomas J.; Uddin, Mohammad Nasir
Abstract: Introduction: Preeclampsia (preE) is characterized by abnormal placentation. Marinobufagenin (MBG), a cardiotonic steroid (CTS), inhibits the function of cytotrophoblast cells (CTBs). We demonstrated that CTSs induce anti-angiogenic and anti-proliferative effects in Sw-71 CTBs. This study tests that CTSs induce apoptotic and stress signaling. Methods: Human extravillous Sw-71 CTBs were incubated with 0, 0.1, 1, 10, and 100 nM of each of three CTSs (MBG, cinobufatalin (CINO) and ouabain (OUB)) for 48 h. Some cells were pretreated with 10 μM p38 mitogen-activated protein kinase (p38 MAPK) inhibitor (SB203580) for 2 h prior to CTSs treatment. We analyzed p38 MAPK phosphorylation, expression of pro-inflammatory protein cyclooxygenase-2 (Cox-2) and ratio of pro-apoptotic Bcl-2-associated X protein (Bax) to anti-apoptotic Bcl-2 protein by western blot in CTSs-treated CTBs lysates. Levels of vascular endothelial growth factor (VEGF), placental growth factor (PlGF), soluble fms-like tyrosine kinase-1 (sFlt-1) and soluble endoglin (sEng) were measured in culture media using ELISA kits. Statistical comparisons were performed using analysis of variance with Duncan's post hoc test. Results: p38 MAPK phosphorylation, expression of Cox-2 and Bax/Bcl-2 was upregulated (*p < 0.05) in CTBs exposed to ≥ 0.1 nM CTSs. Secretion of sFlt-1 and sEng were increased while VEGF and PIGF were decreased in Sw-71 CTBs treated ≥1 nM of each CTSs (*p < 0.01 for each). The SB203580 pretreatment of CTBs significantly attenuated CTS-induced effects. Discussion: Exposure of Sw-71 CTBs to CTSs induced apoptotic and stress signaling and causing anti-angiongenic effect. The observed diminution of CTS-induced signaling by SB203580 pretreatment implicates p38 MAPK as a regulator of these pathways. Highlights: We examine the effect of cardiotonic steroids (CTSs) on cytotrophoblasts (CTBs) function. We evaluate the effects of CTSs on the apoptotic signaling. We examine the effect of CTSs on oxidative stress signaling. p38 MAPK phosphorylation, expression of pro-inflammatory protein Cox-2 and pro-apoptotic Bax/Bcl-2 was upregulated in CTBs exposed to CTSs. Secretion of anti-angiogenic factors (sFlt-1 and sEng) were increased while angiogenic factors (VEGF and PIGF) were decreased in CTBs treated with each CTSs. A p38 inhibitor, SB203580 pretreatment of CTBs significantly attenuated CTS-induced effects.